Room‐Temperature Direct Homolysis of Csp3─H Bond via Catalyst‐Free Photoexcitation - Qi Miao; Meng Liu; Jun Wang; Pan Wu; Changjun Liu; Jian He; Giacomo Lo Zupone; Wei Jiang (Exploration)
ABSTRACT The C─H bond is the most abundant chemical bond in organic compounds. Therefore, the development of the more direct methods for C─H bond cleavage and the elucidation of their mechanisms will provide an important theoretical basis for achieving more efficient C─H functionalization and target molecule construction. In this study, the catalyst‐free photon‐induced direct homolysis of Csp3─H bonds at room temperature was discovered for the first time. The applicable substrate scope of this phenomenon is very wide, expanding from the initial benzyl compounds to aliphatic alcohols, alkanes, olefins, polymers containing benzyl hydrogens, and even gaseous methane. Experiments and calculations have demonstrated that this process involves rapid vibrational relaxation on the femtosecond time scale, leading to the formation of hydrogen radical and carbon radical. Importantly, the direct homolysis of Csp3─H bonds is independent of the presence of oxidants, highlighting its spontaneous nature. Additionally, the cleaved hydrogen radical exhibits diverse reactivity, including coupling reactions to produce hydrogen gas (H2), reduction of oxygen to generate hydrogen peroxide (H2O2), and reduction of carbon dioxide to formic acid (HCOOH). Notably, in the field of H2O2 production, the absence of a catalyst allows for the bypassing of inherent drawbacks associated with photocatalysts, thereby presenting significant potential for practical application. Furthermore, the cleaved carbon radicals display enhanced reactivity, providing excellent opportunities for direct functionalization, thereby enabling efficient C─H bond activation and molecular construction. Overall, this significant discovery offers a valuable new strategy for the production of bulk chemicals, organic synthesis, low‐carbon and hydrogen energy industries, as well as environmental treatment.